Mecanismo da competição intergenotípica em misturas de cultivares de feijão (Phaseolus vulgaris L) - Gastim Pessanha , Gilberto; Vieira , Clibas (Revista Ceres, 2025)
An investigation was carried out to study the mechanisms which regulate the inter-genotypic competition in mixtures of bean (Phaseolus vulgaris L.) cultivars.